Evaluation of Malaysian Corporate Investment Incentives - Barjoyai Bardai (Penerbit Universiti Kebangsaan Malaysia, 1992)
Most policy makers in Third World Countries have postulated the analogous predicament that tax incentives were imperative to investment decision over the last two decades. Such a postulation has spawned attempts by sceptical scholars to evaluate the effectiveness of investment incentives. In this paper several approaches had been used in the evaluation attempt. We started-by comparing incentive programes between the ASEAN countries based on the indifference assumption of foreign investors in terms of location. It has then been extended by observing the cost of doing business as a whole. A more scientific approach has been adopted through the use of trend projections or shift share analysis. It is an attempt to project the excess of investment over normal investment growth in Malaysia. It is identified as the outcome of investment tax incentives programme. Finally an empirical study had also been conducted on 629 companies operating in Malaysia as multinational. Overall, findings from all the analysis above indicate that tax incentives were considered a big stimulant to foreign investment in Malaysia. The survey had also established the crucial role of foreign investment in the robust development of the Malaysian economy over the last decade.